Technologická etapa hrubé stavby pavilonu psychiatrického oddělení v Porubě - Čermák, Matouš (Vysoké učení technické v Brně. Fakulta stavební, 2022)
Cílem zpracování je technologická etapa hrubé stavby pavilonu psychiatrického oddělení v Porubě. Stavba je navržena jako členitý čtyřpodlažní železobetonový skelet nepravidelného půdorysného taru s vnitřním atriem se zastřešením plochými střechami. Nosné konstrukce spodní a horní stavby jsou navrženy jako železobetonový monolitický skelet ztužený stěnami komunikačních jader a jednotlivými monolitickými stěnami. Vodorovné nosné konstrukce jsou tvořeny železobetonovými monolitickými stropními deskami. Obsah práce zahrnuje technickou zprávu, situaci se širšími vztahy dopravních tras, výkaz výměr, technologický předpis pro provádění železobetonových monolitických nosných konstrukcí, technickou zprávu a výkres zařízení staveniště, časový plán, návrh strojních sestav, kontrolní a zkušební plán, bezpečnost práce řešené technologické etapy.

The aim of the processing is the technological stage of the rough construction of the psychiatric ward pavilion in Poruba. The building is designed as a structured four-storey reinforced concrete skeleton of irregular plan with an internal atrium with flat roofs. The load-bearing structures of the lower and upper building are designed as a reinforced concrete monolithic skeleton reinforced by walls of communication cores and individual monolithic walls. The horizontal load-bearing structures are formed by reinforced concrete monolithic floor slabs. The content of the work includes a technical report, a situation with broader relations of transport routes, a statement of dimensions, a technological regulation for the execution of reinforced concrete monolithic load-bearing structures, a technical report and a drawing of the site equipment, a time schedule, a design of machine assemblies, an inspection and testing plan, the safety of the work of the technological stage addressed.
Technological stage of the rough construction of the pavilion of the psychiatric ward in Poruba
Keywords: Psychiatrie; železobetonový monolitický skelet; hrubá vrchní stavba; svislé nosné konstrukce; technologický předpis; systémové bednění; vodorovné nosné konstrukce; časový plán; položkový rozpočet; strojní sestava; bezpečnost a ochrana zdraví při práci.; Psychiatry reinforced concrete monolithic skeleton; rough top construction; vertical load bearing structures; technology code; system formwork; horizontal load bearing structures; time schedule; itemized budget; machine assembly; occupational health and safety.